The History of Articulators: Early Attempts to Reproduce Mandibular Movement - Edgar N. Starcke, DDS (Blackwell Synergy, 2000)
IN 1840, THE FIRST US patents for dental articulators were issued to 2 Philadelphia, PA dentists: James Cameron, on April 30, and Daniel T. Evens,* on August 28. The Cameron Articulator, primarily a hinge-type device, is notable both because it was the first articulator to be patented and because of its unusual pole stand design. The Evens Articulator, however, represented an important advancement in concept.